A binder for a positive electrode of a secondary battery and a method for preparing the same

CN117757041BActive Publication Date: 2026-10-27CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311748030.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-10-27
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

然而,除活性材料外,其他物质对于电池的容量是没有贡献的

Benefits of technology

本发明将二苯并冠醚类单体与N-甲基-4-哌啶酮通过Friedel-Crafts型聚羟基烷基化反应得到线性共聚物,该线性共聚物作为粘合剂时由于含有大量冠醚结构单元,因而可与金属离子配位络合,一方面大量的氧原子有利于粘合剂均匀包裹在活性物质表面,增强界面粘附作用;另一方面,冠醚的强络合作用可以促进电解液中电解质的解离,增强离子导电性;同时N-甲基-4-哌啶酮结构单元中氮原子的孤对电子亦可促进离子的迁移。因此,将本发明制备的线性共聚物作为电极粘合剂使用,可以有效提高电池的倍率性能,并保持较好的长期稳定性。此外,本发明制备的粘合剂可以与其他粘合剂复合使用,将强粘结性与导电性结合起来。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117757041B_ABST
    Figure CN117757041B_ABST
Patent Text Reader

Abstract

The application discloses a kind of secondary battery positive electrode binders and preparation method thereof, belong to secondary battery material and its preparation technical field.The application obtains linear copolymer by polyhydroxyalkylation reaction of diphenyl crown ether monomer and N-methyl-4-piperidone, the copolymer contains a large number of crown ether structure unit, can be coordinated complex with metal ion, on the one hand, it is beneficial to adhesive uniform wrapping in active material surface, enhance interface adhesion;On the other hand, the strong complexation of crown ether can promote electrolyte in electrolyte to dissociate, enhance ion conductivity;While the lone pair of electrons of nitrogen atom in N-methyl-4-piperidone structure unit can also promote ion migration.Therefore, the linear copolymer prepared by the application is used as electrode adhesive, can effectively improve the rate capability of battery, and keep good long-term stability.In addition, the adhesive prepared by the application can be used with other adhesives, combine strong adhesion with conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a binder for the positive electrode of a secondary battery and its preparation method, belonging to the field of secondary battery materials and their preparation technology. Background Technology

[0002] With the rapid development of energy structure transformation, rechargeable batteries have received increasing attention. Among various energy storage devices, lithium-ion batteries have many advantages such as high energy density and long cycle life, and are currently widely used in various energy storage power systems such as electric vehicles, aerospace, wind power, and thermal power. Furthermore, as the application of lithium-ion batteries matures, sodium-ion and potassium-ion batteries, with similar working principles, show great development potential due to abundant sodium / potassium resources. Battery performance largely depends on the electrodes; optimizing battery structure is beneficial to promoting the development of high-performance batteries.

[0003] The positive electrode of the aforementioned secondary batteries is composed of active materials, binders, conductive agents, and current collectors. The binder's role is to tightly bond the active materials and conductive agents to the current collector. Since the active materials and conductive agents are generally in powder form, they cannot be fixed to the current collector solely on their own. Powdering and detachment of the electrode would lead to capacity loss and interruption of electron and ion transfer, which is fatal to the normal operation of the battery. Therefore, the binder is crucial for maintaining electrode integrity, ion transfer, and effective electrochemical reactions.

[0004] Currently, existing technologies have disclosed various novel adhesives to address the shortcomings of the aforementioned adhesives. For example, Chinese patent CN116731635A discloses a conductive adhesive prepared by reacting an aqueous solution of sodium carboxymethyl cellulose, polyacrylic acid, and other polymers rich in carboxyl and hydroxyl groups with ligands (Congo red, aniline black, and amino black) through heating. The presence of polar groups increases the adhesion to active materials, and the large number of amino and hydroxyl groups enhances the electron cloud density, giving the polymer an electronic conjugation effect and providing a certain degree of electronic conductivity. Chinese patent CN116404164A discloses a strip-shaped graphene with a large aspect ratio, rich in carboxyl and hydroxyl groups at its edges, to achieve coupling between the adhesive and the conductive agent, reducing the proportion of inactive materials in the electrode sheet. Simultaneously, its three-dimensional extended structure provides abundant mass transfer channels. Chinese patent CN116814187A also discloses a raspberry-type core-shell structure composite particle with a spherical conductive particle core and a polymer shell. The research approach of these adhesives tends to pursue the goal of achieving both adhesion and conductivity. However, these adhesives still suffer from limited conductivity, insufficient adhesion, and restricted application scenarios. Therefore, it is essential to develop new adhesives that possess both adhesion and conductivity.

[0005] An ideal adhesive should have the following characteristics: (1) good solubility, that is, it can dissolve quickly and fully during the preparation of the adhesive solution to avoid the formation of polymer agglomeration, which would affect the dispersion of active materials and ion transport; (2) large molecular weight, which can provide sufficient adhesion even with reduced adhesive dosage; (3) stable slurry state; (4) strong adhesion to active materials, conductive agents and current collectors, that is, the peel strength of the prepared electrode sheet is large; (5) stable electrochemical properties to avoid side reactions during battery operation; (6) suppressing the swelling effect of electrolyte and maintaining the integrity of the electrode sheet; (7) good flexibility to withstand the bending of the electrode sheet during production and the volume change of active material particles during charging and discharging; (8) good conductivity, etc.

[0006] However, existing adhesives only meet some of the above requirements. Taking the common adhesive polyvinylidene fluoride (PVDF) as an example, because it has a linear structure and lacks polar groups, PVDF mainly relies on intermolecular forces for adhesion. Some active materials undergo large volume changes or mass migration during battery operation, making such adhesives far from sufficient. During long-term charge-discharge cycles, the positive electrode may crack or even pulverize, leading to deterioration in battery performance. Furthermore, the active materials themselves are not conductive, requiring the introduction of conductive agents to ensure smooth charge transfer. However, apart from the active materials, other substances do not contribute to the battery's capacity. Patent CN116404164A mentions that increasing the content of insulating adhesive in the slurry will restrict the overall conductivity of the electrode sheet.

[0007] In summary, developing adhesives that combine good adhesion and excellent conductivity is beneficial for improving the long-term cycle stability and rate performance of batteries. Summary of the Invention

[0008] In order to solve the above-mentioned technical problems of the adhesives used in the positive electrode of secondary batteries, the present invention provides an adhesive for the positive electrode of secondary batteries and a method for preparing the same.

[0009] The technical solution of the present invention: One objective of this invention is to provide a method for preparing an electrode binder, the method comprising the following steps: (1) After mixing the dibenzocrown ether monomer, N-methyl-4-piperidinone, trifluoroacetic acid and Eaton reagent evenly, the polymerization reaction was carried out at room temperature; (2) After the polymerization reaction is completed, the reaction solution is poured into potassium hydroxide aqueous solution, the precipitated solid is collected, and it is thoroughly washed with deionized water and dried. The product is the binder.

[0010] Further specifying, the dibenzocrown ether monomers are one or more of the following: dibenzo-12-crown ether-4, dibenzo-15-crown ether-5, dibenzo-18-crown ether-6, dibenzo-21-crown-7, and dibenzo-24-crown ether-8.

[0011] To further specify, the dibenzocrown ether monomers are dibenzo-18-crown-6 and dibenzo-15-crown-5.

[0012] To further specify, the dibenzocrown ether monomers are dibenzo-15-crown-5 and dibenzo-12-crown-ether-4.

[0013] Furthermore, when the dibenzocrown ether monomer is dibenzo-12-crown ether-4, the resulting binder is more suitable for lithium-ion secondary batteries.

[0014] Furthermore, when the dibenzocrown ether monomer is dibenzo-15-crown ether-5, the resulting binder is more suitable for sodium-ion secondary batteries.

[0015] Furthermore, when the dibenzocrown ether monomer is dibenzo-18-crown ether-6, the resulting binder is more suitable for potassium-ion secondary batteries.

[0016] Further specifying, the ratio of dibenzocrown ether monomers, N-methyl-4-piperidinone, trifluoroacetic acid and Eaton reagent is: (1.5~1.8) mol: 1 mol: (2.7~3.7) mL: (12.1~13.1) mL.

[0017] Further specifying, the solid content of the polymerization system is 20-50%.

[0018] Furthermore, the solid content of the polymerization system is specified to be 30-40%.

[0019] Further specifying, Eaton reagent is a mixture of methanesulfonic acid and phosphorus pentoxide in a mass ratio of 12:1.

[0020] Further specified, the dibenzocrown ether monomer, N-methyl-4-piperidinone, trifluoroacetic acid and Eaton reagent are mixed uniformly at 0°C.

[0021] Further limiting, the polymerization reaction time is 24~48h.

[0022] Furthermore, the polymerization reaction time is specified to be 30-48 hours.

[0023] Furthermore, the concentration of the potassium hydroxide aqueous solution is specified as 1M.

[0024] A second objective of this invention is to provide an adhesive obtained by the above preparation method, the structural formula of which is as follows: .

[0025] The third objective of this invention is to provide an application of the binder obtained by the above preparation method, specifically for the preparation of the positive electrode sheet of a secondary battery.

[0026] Further specifying, the preparation method of the positive electrode sheet of the secondary battery includes the following steps: (1) The above-mentioned adhesive is added to N-methylpyrrolidone solvent to prepare an adhesive solution; (2) According to the mass ratio of active material, conductive agent and binder of (80~95):(10~2):(10~3), add active material and conductive agent to binder solution and mix evenly to obtain positive electrode slurry; (3) The positive electrode slurry is scraped onto the current collector and then dried and rolled to obtain the positive electrode sheet.

[0027] Further specifying, the concentration of the adhesive solution is 20~40 mg / mL.

[0028] Further specifying, the mass ratio of active material, conductive agent and adhesive is (90~95):(5~2):(5~3).

[0029] Further specified, the above-mentioned adhesive and the adhesive containing polar groups are used in combination at a mass ratio of (50~100):(0~50).

[0030] To further specify, the mass ratio is (70:30):(60:40).

[0031] Furthermore, the binder containing polar groups is an acrylic homopolymer or copolymer.

[0032] Beneficial effects: This invention relates to a linear copolymer obtained by reacting dibenzocrown ether monomers with N-methyl-4-piperidinone via a Friedel-Crafts-type polyhydroxyalkylation reaction. When used as an electrode binder, this linear copolymer, due to its abundant crown ether structural units, can coordinate and complex with metal ions. On one hand, the large number of oxygen atoms facilitates uniform coating of the binder on the surface of the active material, enhancing interfacial adhesion. On the other hand, the strong complexation of the crown ether promotes the dissociation of electrolyte in the electrolyte, enhancing ionic conductivity. Simultaneously, the lone pair electrons of the nitrogen atoms in the N-methyl-4-piperidinone structural units also promote ion migration. Therefore, using the linear copolymer prepared by this invention as an electrode binder can effectively improve the rate performance of the battery and maintain good long-term stability. Furthermore, the binder prepared by this invention can be used in combination with other binders, combining strong adhesion with conductivity.

[0033] This invention utilizes the characteristic that crown ethers preferentially select cations with cavities closest to their own and secondarily select cations with cavities slightly larger than their own. Different crown ether structures are combined to form polymers as binders. By using combined crown ethers, the crown ether rings are less prone to folding, twisting, and conformational changes, thereby fully leveraging the complexing effect of the crown ether structure and increasing its competitiveness against alkali metal ions in the system. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the adhesive bonding state prepared according to the present invention; Figure 2 The proton NMR spectrum of the adhesive prepared in Example 1; Figure 3 A scanning electron microscope image of the positive electrode sheet prepared in Application Example 1; Figure 4 The graph shows a comparison of the peeling performance of the positive electrode sheets prepared in Application Example 1, Application Example 2 and Comparative Example 1. Figure 5 The graph shows a comparison of the cycle performance of the batteries prepared in Application Example 1, Application Example 2 and Comparative Example 1. Figure 6 The graph shows a comparison of the rate performance of the batteries prepared in Application Example 1, Application Example 2, and Comparative Example 1. Detailed Implementation

[0035] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0036] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0038] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0039] Example 1: Dibenzo-18-crown-6 (10 mmol), N-methyl-4-piperidinone (10 mmol), trifluoroacetic acid (3.2 mL), and Eaton reagent (12.6 mL) were sequentially added to a single-necked flask at 0 °C and magnetically stirred. After thorough mixing, the mixture was heated to room temperature to initiate the polymerization reaction. After 31 h of reaction, the viscous reaction solution was slowly poured into an aqueous solution containing 1 M potassium hydroxide (approximately 1000 mL), and the precipitated solid was collected. The precipitated solid product was thoroughly washed with deionized water and then dried under vacuum to obtain the binder.

[0040] The obtained adhesive polymer was characterized by proton nuclear magnetic resonance spectroscopy, and the results are as follows: Figure 2 As shown.

[0041] Example 2: Dibenzo-15-crown ether-5 (10 mmol), N-methyl-4-piperidinone (10 mmol), trifluoroacetic acid (2.9 mL), and Eaton reagent (11.4 mL) were sequentially added to a single-necked flask at 0 °C and magnetically stirred. After thorough mixing, the mixture was heated to room temperature to initiate the polymerization reaction. After 28 h of reaction, the viscous reaction solution was slowly poured into an aqueous solution containing 1 M potassium hydroxide (approximately 1000 mL), and the precipitated solid was collected. The precipitated solid product was thoroughly washed with deionized water and then dried under vacuum to obtain the binder.

[0042] Example 3: Dibenzo-12-crown ether-4 (10 mmol), N-methyl-4-piperidinone (10 mmol), trifluoroacetic acid (2.6 mL), and Eaton reagent (10.2 mL) were sequentially added to a single-necked flask at 0 °C and magnetically stirred. After thorough mixing, the mixture was heated to room temperature to initiate the polymerization reaction. After 27 h of reaction, the viscous reaction solution was slowly poured into an aqueous solution containing 1 M potassium hydroxide (approximately 1000 mL), and the precipitated solid was collected. The precipitated solid product was thoroughly washed with deionized water and then dried under vacuum to obtain the binder.

[0043] Example 4: Dibenzo-18-crown-6 (5 mmol), dibenzo-15-crown-ether-5 (5 mmol), N-methyl-4-piperidinone (10 mmol), trifluoroacetic acid (3 mL), and Eaton reagent (12 mL) were sequentially added to a single-necked flask at 0 °C and magnetically stirred. After thorough mixing, the mixture was heated to room temperature to initiate the polymerization reaction. After 30 h of reaction, the viscous reaction solution was slowly poured into an aqueous solution containing 1 M potassium hydroxide (approximately 1000 mL), and the precipitated solid was collected. The precipitated solid product was thoroughly washed with deionized water and then dried under vacuum to obtain the binder.

[0044] Example 5: Dibenzo-15-crown-5 (5 mmol), dibenzo-12-crown-ether-4 (5 mmol), N-methyl-4-piperidinone (10 mmol), trifluoroacetic acid (2.8 mL), and Eaton reagent (10.8 mL) were sequentially added to a single-necked flask at 0 °C and magnetically stirred. After thorough mixing, the mixture was heated to room temperature to initiate the polymerization reaction. After 28 h of reaction, the viscous reaction solution was slowly poured into an aqueous solution containing 1 M potassium hydroxide (approximately 1000 mL), and the precipitated solid was collected. The precipitated solid product was thoroughly washed with deionized water and then dried under vacuum to obtain the binder.

[0045] Application Example 1: The adhesive from Example 1 was used as a binder for lithium iron phosphate to prepare the positive electrode sheet for lithium-ion batteries.

[0046] A 25 mg / mL binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution to achieve a conductive agent concentration of 25 mg / mL. After thorough mixing, lithium iron phosphate was added to achieve an active material concentration of 200 mg / mL. The mixture was then stirred uniformly to obtain the positive electrode slurry. Lithium iron phosphate electrode sheets were then prepared through coating, baking, and rolling. Figure 1 This is a schematic diagram of the adhesive bonding state. In a glove box, the positive electrode sheet, positive and negative electrode shells, gaskets, spring contacts, lithium sheets, separator, and electrolyte are assembled into a coin cell and left to stand for 12 hours to ensure full immersion inside the battery.

[0047] The scanning electron microscope (SEM) image of the positive electrode sheet prepared in this application example is shown below. Figure 3 As shown, by Figure 3 As can be seen from the scanning electron microscope image, the adhesive can uniformly encapsulate the active material.

[0048] Application Example 2: The binder from Example 1 was combined with an acrylonitrile copolymer (mass ratio 60:40) as a binder for lithium iron phosphate to prepare the positive electrode sheet for lithium-ion batteries.

[0049] A 25 mg / mL binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution to achieve a concentration of 25 mg / mL. After thorough mixing, lithium iron phosphate was added to achieve an active material concentration of 200 mg / mL. The mixture was then stirred uniformly to obtain a positive electrode slurry. Lithium iron phosphate electrodes were then prepared through coating, baking, and rolling. In a glove box, the positive electrode, along with the positive and negative electrode shells, gaskets, spring contacts, lithium foil, separator, and electrolyte, were assembled into a coin cell and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0050] Application Example 3: The adhesive from Example 2 was used as a binder for lithium iron phosphate to prepare the positive electrode sheet for lithium-ion batteries.

[0051] A 25 mg / mL binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution to achieve a concentration of 25 mg / mL. After thorough mixing, lithium iron phosphate was added to achieve an active material concentration of 200 mg / mL. The mixture was then stirred uniformly to obtain a positive electrode slurry. Lithium iron phosphate electrodes were then prepared through coating, baking, and rolling. In a glove box, the positive electrode, along with the positive and negative electrode shells, gaskets, spring contacts, lithium foil, separator, and electrolyte, were assembled into a coin cell and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0052] Application Example 4: The adhesive from Example 3 was used as a binder for lithium iron phosphate to prepare the positive electrode sheet for lithium-ion batteries.

[0053] A 25 mg / mL binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution to achieve a concentration of 25 mg / mL. After thorough mixing, lithium iron phosphate was added to achieve an active material concentration of 200 mg / mL. The mixture was then stirred uniformly to obtain a positive electrode slurry. Lithium iron phosphate electrodes were then prepared through coating, baking, and rolling. In a glove box, the positive electrode, along with the positive and negative electrode shells, gaskets, spring contacts, lithium foil, separator, and electrolyte, were assembled into a coin cell and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0054] Application Example 5: The adhesive from Example 4 was used as a binder for lithium iron phosphate to prepare the positive electrode sheet for lithium-ion batteries.

[0055] A 25 mg / mL binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution to achieve a concentration of 25 mg / mL. After thorough mixing, lithium iron phosphate was added to achieve an active material concentration of 200 mg / mL. The mixture was then stirred uniformly to obtain a positive electrode slurry. Lithium iron phosphate electrodes were then prepared through coating, baking, and rolling. In a glove box, the positive electrode, along with the positive and negative electrode shells, gaskets, spring contacts, lithium foil, separator, and electrolyte, were assembled into a coin cell and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0056] Application Example 6: The adhesive from Example 5 was used as a binder for lithium iron phosphate to prepare the positive electrode sheet for lithium-ion batteries.

[0057] A 25 mg / mL binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution to achieve a concentration of 25 mg / mL. After thorough mixing, lithium iron phosphate was added to achieve an active material concentration of 200 mg / mL. The mixture was then stirred uniformly to obtain a positive electrode slurry. Lithium iron phosphate electrodes were then prepared through coating, baking, and rolling. In a glove box, the positive electrode, along with the positive and negative electrode shells, gaskets, spring contacts, lithium foil, separator, and electrolyte, were assembled into a coin cell and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0058] Application Example 7: Sodium-ion battery positive electrode sheets were prepared using the adhesive from Example 1 as a binder for layered oxides.

[0059] A 3% solids content binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution, and after thorough mixing, layered oxides were added. The mass ratio of binder, conductive agent, and active material was 3:2:95. The mixture was stirred uniformly to obtain a positive electrode slurry. The positive electrode sheet was then prepared by coating, baking, and rolling. In a glove box, the positive electrode sheet was assembled with the positive and negative electrode shells, gaskets, springs, lithium sheets, separators, and electrolyte to form a coin cell, and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0060] Application Example 8: The adhesive from Example 1 was used to combine with an acrylonitrile copolymer (mass ratio 60:40) as an adhesive for layered oxides to prepare the positive electrode sheet for sodium-ion batteries.

[0061] A 3% solids content binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution, and after thorough mixing, layered oxides were added. The mass ratio of binder, conductive agent, and active material was 3:2:95. The mixture was stirred uniformly to obtain a positive electrode slurry. The positive electrode sheet was then prepared by coating, baking, and rolling. In a glove box, the positive electrode sheet was assembled with the positive and negative electrode shells, gaskets, springs, lithium sheets, separators, and electrolyte to form a coin cell, and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0062] Application Example 9: Sodium-ion battery positive electrode sheets were prepared using the adhesive from Example 2 as a binder for layered oxides.

[0063] A 3% solids content binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution, and after thorough mixing, layered oxides were added. The mass ratio of binder, conductive agent, and active material was 3:2:95. The mixture was stirred uniformly to obtain a positive electrode slurry. The positive electrode sheet was then prepared by coating, baking, and rolling. In a glove box, the positive electrode sheet was assembled with the positive and negative electrode shells, gaskets, springs, lithium sheets, separators, and electrolyte to form a coin cell, and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0064] Application Example 10: Sodium-ion battery positive electrode sheets were prepared using the adhesive from Example 3 as a binder for layered oxides.

[0065] A 3% solids content binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution, and after thorough mixing, layered oxides were added. The mass ratio of binder, conductive agent, and active material was 3:2:95. The mixture was stirred uniformly to obtain a positive electrode slurry. The positive electrode sheet was then prepared by coating, baking, and rolling. In a glove box, the positive electrode sheet was assembled with the positive and negative electrode shells, gaskets, springs, lithium sheets, separators, and electrolyte to form a coin cell, and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0066] Application Example 11: Sodium-ion battery positive electrode sheets were prepared using the adhesive from Example 4 as a binder for layered oxides.

[0067] A 3% solids content binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution, and after thorough mixing, layered oxides were added. The mass ratio of binder, conductive agent, and active material was 3:2:95. The mixture was stirred uniformly to obtain a positive electrode slurry. The positive electrode sheet was then prepared by coating, baking, and rolling. In a glove box, the positive electrode sheet was assembled with the positive and negative electrode shells, gaskets, springs, lithium sheets, separators, and electrolyte to form a coin cell, and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0068] Application Example 12: Sodium-ion battery positive electrode sheets were prepared using the adhesive from Example 5 as a binder for layered oxides.

[0069] A 3% solids content binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution, and after thorough mixing, layered oxides were added. The mass ratio of binder, conductive agent, and active material was 3:2:95. The mixture was stirred uniformly to obtain a positive electrode slurry. The positive electrode sheet was then prepared by coating, baking, and rolling. In a glove box, the positive electrode sheet was assembled with the positive and negative electrode shells, gaskets, springs, lithium sheets, separators, and electrolyte to form a coin cell, and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0070] Comparative Example 1: Lithium-ion battery positive electrode sheets were prepared using conventional polyvinylidene fluoride adhesive as the binder for lithium iron phosphate.

[0071] A 25 mg / mL binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution to achieve a concentration of 25 mg / mL. After thorough mixing, lithium iron phosphate was added to achieve an active material concentration of 200 mg / mL. The mixture was then stirred uniformly to obtain a positive electrode slurry. Lithium iron phosphate electrodes were then prepared through coating, baking, and rolling. In a glove box, the positive electrode, along with the positive and negative electrode shells, gaskets, spring contacts, lithium foil, separator, and electrolyte, were assembled into a coin cell and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0072] Comparative Example 2: Sodium-ion battery positive electrode sheets were prepared using conventional polyvinylidene fluoride adhesive as the binder for layered oxides.

[0073] A 3% solids content binder solution was prepared using N-methylpyrrolidone as the solvent. A conductive agent was added to the binder solution, and after thorough mixing, layered oxides were added. The mass ratio of binder, conductive agent, and active material was 3:2:95. The mixture was stirred uniformly to obtain a positive electrode slurry. The positive electrode sheet was then prepared by coating, baking, and rolling. In a glove box, the positive electrode sheet was assembled with the positive and negative electrode shells, gaskets, springs, lithium sheets, separators, and electrolyte to form a coin cell, and allowed to stand for 12 hours to ensure complete internal wetting of the battery.

[0074] Example of results: (1) The peeling performance of the positive electrode sheets prepared in corresponding use case 1, application example 2 and comparative example 1 was tested, and the test results are as follows: Figure 4 As shown, by Figure 4 It can be seen that, compared with PVDF adhesives, the adhesives prepared and the adhesive systems used in combination have improved and enhanced adhesion.

[0075] (2) The lithium metal button half-cells prepared in Application Examples 1-6 and Comparative Example 1 were subjected to electrochemical cycle performance tests. They were first activated for 3 cycles at a current density of 0.08C, and then cycled at 1C. The electrochemical cycle performance of Application Examples 1, Application Example 2, and Comparative Example 1 was as follows: Figure 5 As shown (activation cycles omitted), the battery's rate performance was tested within a current range of 0.02C to 5C. The test results are as follows. Figure 6 (Activation cycles are omitted as shown).

[0076] Table 1 compares the electrochemical and rate performance of lithium metal half-cells: Table 1

[0077] Electrochemical cycle performance tests were conducted on the sodium metal button half-cells prepared in Application Examples 7-12 and Comparative Example 2, and on the lithium metal button half-cells prepared in Application Examples 1-6 and Comparative Example 1. Rate performance tests were also conducted on the cells within a current range of 0.02C to 5C. The results are shown in Table 2 below. Table 2

[0078] In summary, the adhesive prepared using this invention exhibits excellent ion conductivity, and a significant improvement is evident in the application examples during long-term cycling. Battery performance is also improved in rate performance tests.

[0079] Furthermore, using a combination of crown ethers as a binder improves the effect more significantly. This is because different crown ether cavities and alkali metal ions of different diameters are matched with each other, and different crown ether structures have different complexation states with metal ions of different diameters. Combining different crown ether structures to use polymers as binders can give full play to the complexation effect of crown ether structures and increase their competitiveness against alkali metal ions in the system.

[0080] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. A method for preparing an electrode binder, characterized in that, include: (1) After mixing dibenzocrown ether monomers, N-methyl-4-piperidinone, trifluoroacetic acid and Eaton reagent evenly, the polymerization reaction was carried out at room temperature; the dibenzocrown ether monomers were one or a mixture of dibenzo-12-crown ether-4, dibenzo-15-crown ether-5, and dibenzo-18-crown ether-6; (2) After the polymerization reaction is completed, the reaction solution is poured into potassium hydroxide aqueous solution, the precipitated solid is collected, and it is thoroughly washed with deionized water and dried. The product is the binder.

2. The preparation method according to claim 1, characterized in that, The dibenzocrown ether monomers are dibenzo-18-crown-6 and dibenzo-15-crown-5.

3. The preparation method according to claim 1, characterized in that, The dibenzocrown ether monomers are dibenzo-15-crown-5 and dibenzo-12-crown-ether-4.

4. The preparation method according to claim 1, characterized in that, The ratio of dibenzocrown ether monomers, N-methyl-4-piperidinone, trifluoroacetic acid and Eaton reagent is (1.5~1.8) mol: 1 mol: (2.7~3.7) mL: (12.1~13.1) mL.

5. The preparation method according to claim 1, characterized in that, Eaton reagent is a mixture of methanesulfonic acid and phosphorus pentoxide in a mass ratio of 12:

1.

6. The preparation method according to claim 1, characterized in that, Dibenzocrown ether monomers, N-methyl-4-piperidinone, trifluoroacetic acid, and Eaton reagent were mixed uniformly at 0°C, and the polymerization reaction time was 24-48 h.

7. An adhesive obtained by the preparation method according to any one of claims 1-6.

8. The application of the adhesive according to claim 7, characterized in that, Preparation of positive electrode sheets for secondary batteries.

9. A method for preparing a positive electrode sheet for a secondary battery, characterized in that, include: (1) The adhesive of claim 7 and the adhesive containing polar groups are added to N-methylpyrrolidone solvent at a mass ratio of (50~100):(0~50) to prepare an adhesive solution; (2) According to the mass ratio of active material, conductive agent and binder of (80~95):(10~2):(10~3), add active material and conductive agent to binder solution and mix evenly to obtain positive electrode slurry; (3) The positive electrode slurry is scraped onto the current collector and then dried and rolled to obtain the positive electrode sheet.

Citation Information

Patent Citations

  • Conductive binder for battery negative electrode and preparation method of conductive binder

    CN116404164A

  • Conductive binder as well as preparation method and application thereof

    CN116731635A

  • Water-based conductive binder as well as preparation method and application thereof

    CN116814187A

  • Isatin aromatic hydrocarbon copolymer, preparation method and application thereof

    CN110903449A

  • Preparation method of polymer binder containing basic group and application of polymer binder in high-temperature fuel cell

    CN115558085A